Review and Comparison of Electronic Patient‐Facing Family Health History Tools. Issue 2 (6th March 2018) - Welch, Brandon M.; Wiley, Kevin; Pflieger, Lance; Achiangia, Rosaline; Baker, Karen; Hughes‐Halbert, Chanita; Morrison, Heath; Schiffman, Joshua; Doerr, Megan
Abstract: Family health history (FHx) is one of the most important pieces of information available to help genetic counselors and other clinicians identify risk and prevent disease. Unfortunately, the collection of FHx from patients is often too time consuming to be done during a clinical visit. Fortunately, there are many electronic FHx tools designed to help patients gather and organize their own FHx information prior to a clinic visit. We conducted a review and analysis of electronic FHx tools to better understand what tools are available, to compare and contrast to each other, to highlight features of various tools, and to provide a foundation for future evaluation and comparisons across FHx tools. Through our analysis, we included and abstracted 17 patient‐facing electronic FHx tools and explored these tools around four axes: organization information, family history collection and display, clinical data collected, and clinical workflow integration. We found a large number of differences among FHx tools, with no two the same. This paper provides a useful review for health care providers, researchers, and patient advocates interested in understanding the differences among the available patient‐facing electronic FHx tools.